Requirements for robots in combined passenger/freight transport - Marko Thiel; Sandra Tjaden; Manuel Schrick; Kerstin Rosenberger; Matthias Grote (Adapting to the Future: Maritime and City Logistics in the Context of Digitalization and Sustainability. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 32, 2021)
Purpose: Delivery robots promise to provide gains in logistics in many ways especially on short distances. However, there is a lack of orderly overview of requirements for their successful implementation. The aim of this paper is to generate a better understanding of how to implement delivery robots in public infrastructure. Methodology: This paper follows an explorative, applied and interdisciplinary research approach based on the pilot project 'TaBuLa-LOG'. The results of a literature review were used as the foundation for thematically targeted expert workshops, interviews and desktop research. The individual approaches and outlined requirements are then combined and structured on the basis of a dependency model. Findings: We discuss not only the independent solo autonomous use of delivery robots, but also the combined use, where the main run takes place in an automated passenger shuttle. The result of this paper is a comprehensive overview of the identified requirements structured along the developed dependency model. Originality: When it comes to delivery robots there is limited uniform information about the implementation in real environments so far. This paper closes the gap by identifying requirements for implementing a delivery robot into a combined passenger and freight transport.
urn:nbn:de:gbv:830-882.0162267; hdl:10419/249609; https://econpapers.repec.org/RePEc:zbw:hiclpr:32
Keywords: 650; City Logistics